(untitled) (Pedagogy of Higher and Secondary Education, 2017)
The article deals with the problem of defining the role of education in the formation and development of Ukrainian Kozakdom. There are described political, socio-economic, cultural and religious conditions of the development of Ukrainian society in the 16-18 centuries. It is noted that after the Union of Lublin in 1569 Ukrainian society suffered from offensive of Catholicism, spreading of serfdom and Polonization. The answer of the Ukrainian people was the growth of the authority and role of Cossacks – the only capable force that can put an end to the assimilation of the Ukrainian nation. The article examines the concepts of Ukrainian Cossacks and investigates the causes of activation of educational policy in Ukrainian society in the last quarter of the 16th century. These reasons were destructive educational activities of the Jesuits, renegacy of Ukrainian elite, urgent need to protect the natural rights of the Ukrainian eople. It is found that education contributed to the formation of Kozakdom as a powerful military and political force of Ukrainian society, due to education there appeared real leaders among the Cossacks, endowed with well-developed intellect, moral virtues, military capabilities. In this research there was elicited a link between the spread of education and the development of Ukrainian Cossacks, there were given historical examples of prominent representatives of Cossack elders and found the reasons for their success in the context of the education they had received. The information of the article proves that the education was very popular among different classes of Ukrainian society in the 17-18th centuries, it allowed to create the best examples of a democratic social order of the Zaporozhian Sich Republic. In the future it made possible to establish a network of schools in Zaporizhzhya where future Cossacks were taught to read, write, count, music, poetry; students achieved significant success in physical training, military and sports training, mastered the basics of traditional medicine and astronomy.The result of a combination of military valor and educational training was the development of the chivalric code, which the Cossacks guided in everyday life. The Ukrainian Cossacks in their history constantly demonstrated the benefits of education and thus achieved significant diplomatic successes and victories over enemies.